Plazma ARC joining of thin plate constructions - Valiulis, A. V. (Journal of Civil Engineering and Management, 1995)
Heat and fluid flow exist not only in ingots or big size welds but also in small size microplasma ARC melted weld pool. Edge weld pool geometry depend from interfacial energy, direction of the fluid flows in the weld pool caused by thermocapilary convection. Thermocapilary convection is the dominant flow mechanism under downhand welding conditions. Comparision are made between calculated size of edge weld and experimental results.Article in Lithuanian.Plazminis plonalakščių konstrukcuijų sujungimasFirst Published Online: 26 Jul 2012